Creative Thinking Development to Foster Economic Creative: Evidence of State University of Surabaya - Subroto, Waspodo Tjipto (International Review of Management and Marketing, 2015)
Development skill of creative thinking is very urgent to foster economic creative in economic education. Economic education the needs of problem base learning with scientific approach to foster economic creative and thinking skill of students in faculty of economic. The purposes of these studies were: (a) development thinking skill to foster economic creative of students, (b) development problem base learning to increase creative thinking, (c) applied scientific approach for development economic creative to foster student’s abilities in faculty of economic. The results of these studies have been developed: (1) development thinking skills tools increase creative economic abilities of student in faculty of economic, (2) problem base learning to increase creative thinking, (3) scientific approach can be tools to foster student abilities and increase quality of economic education. Keywords: thinking skill, problem base learning, economic creative. JEL Classifications: A2